A Case of a C-Stem Fracture at the Head-Neck Junction and a Review of the Literature. (9th December 2012) - Morley, David; Starks, Ian; Lim, Justin
Abstract : We report the first case of a fracture of the standard C-stem in combination with a large metal-on-metal articulation. This occurred at the head-neck junction. Analysis of the fractured stem showed evidence of fatigue failure with possible corrosion. The use of large femoral heads with neck adaptors and narrow tapers should be used with caution, especially in heavy, active patients.